Long term safety of etanercept in elderly subjects with rheumatic diseases. Issue 3 (8th September 2005) - Fleischmann, R; Baumgartner, S W; Weisman, M H; Liu, T; White, B; Peloso, P
Abstract : Objectives: To determine the long term safety profile of the tumour necrosis factor (TNF) antagonist etanercept in subjects with rheumatoid arthritis (RA), psoriatic arthritis (PsA), or ankylosing spondylitis (AS) aged ⩾65 years in comparison with subjects aged <65 years. Methods: Safety data from an integrated database of 4322 subjects enrolled in 18 RA trials, 2 PsA trials, and 2 AS trials were analysed. Safety end points included subject incidence of all adverse events (AE), serious adverse events (SAE), infectious events (IE), medically important infections (MII), and deaths. Events of particular interest in subjects treated with TNF modulating biological treatments, including demyelinating diseases, tuberculosis, lymphomas, and cardiovascular diseases, were also evaluated. Results: The incidence of AE, SAE, IE, MII, and malignancies was not significantly raised in elderly subjects in comparison with subjects aged <65 years. No cases of tuberculosis were reported in the trials. Demyelinating diseases were seen only in subjects aged <65 years. The incidence and types of death in the elderly subjects were consistent with the expected rates for subjects of comparable age. Conclusions: Etanercept is a generally safe and well tolerated biological agent for treatment of rheumatological diseases in the elderly, and the risk of AE in these studies was no greater in subjects aged ⩾65 years than in younger subjects.